Strategi Pencahayaan Buatan Dalam Adaptasi Kebiasaan Baru; Studi Kasus Rumah Tinggal HUNI - Abdulhadi, Reza Hambali Wilman; Bella, Annisa (Program Studi Desain Interior Unikom, 2021)
During COVID-19 pandemic, a house is no longer just a place to live, but also used for various activities; a place to protect from potential transmission of the corona virus. To prevent virus spreading, we need to stay at home as much as possible. During pandemic people are advised to stay at home, but there are times when residents need to leave the house. From the activities carried outside the house, possibilities of bacteria and viruses which brought into the house through items used or carried is emminent. To overcome this, a strategy is needed to reduce exposure of bacteria and viruses from outside the house. One way that can be done is through artificial lighting strategies to disinfect items. Artificial lighting is any source of light that does not come from nature and consumes energy. In relation to the prevention and spread of the corona virus, it is known that UVC rays are a type of light wave that can be used to kill the corona virus. This research was conducted through a data driven method, to see what possibilities could be done to prevent the spread of the virus at home. The object of study used in this case is the HUNI residence, which is a modular residential concept and can be easily configured to allow zoning in the house to be replaced as needed. Through this research, the concept of a sterilizer using UVC light was formed that could meet the needs of the new normal. With the presence of a sterilizer, it is hoped that it can be a way to prevent the spread of bacteria and viruses into the home.